Waterproof tear-resistant modified polyurethane for artificial leather and method for preparing the same
Patent Information
- Application Number
- CN202611425813.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-16
AI Technical Summary
二是抗撕裂强度较低
[0023]This invention constructs a branched hydroxyl-terminated polyester, which is then polymerized with isocyanate and chain extender to obtain a modified polyurethane for artificial leather. The branched structure has a large number of three-dimensionally outward-extending branches, forming physical-chemical nodes distributed in the resin matrix. The three-dimensional branched spatial structure formed by crosslinking after branching can deflect and bifurcate the expanding crack when the material is subjected to tearing force, thus consuming the crack propagation fracture energy. Furthermore, by constructing a multi-functional crosslinking network, it disperses the external force and inhibits crack propagation, thereby improving the tear resistance of the material. However, during testing, it was found that although it possessed a certain degree of tear resistance, its waterproof performance deteriorated. This may be because while the introduction of branched structures can improve tear resistance by dispersing external forces through a three-dimensional network structure, it also disrupts the regularity of polyurethane molecular chains, thereby affecting the crystallinity during polyurethane synthesis. This could lead to an increase in the amorphous regions for water molecule diffusion. Further increasing the degree of branching can increase the crosslinking density and inhibit molecular chain movement, thus achieving waterproof performance. However, excessive branching and resulting dense crosslinking may cause excessive local rigidity, creating stress concentration points that are prone to cracking under external forces, thus compromising tear resistance. Therefore, this invention uses cellulose nanocrystals as a nucleating agent to enhance the crystallinity of polyurethane. The nucleation effect of cellulose nanocrystals improves the crystallinity of polyurethane, resulting in a tightly packed internal structure that hinders water molecule penetration. However, direct use is problematic because cellulose nanocrystals have poor interfacial compatibility with polyurethane, and the surface of cellulose nanocrystals contains numerous hydroxyl groups that can form hydrogen bonds with water molecules. This not only hinders the improvement of waterproof performance but also weakens tear resistance. To this end, the present invention modifies cellulose nanocrystals by acylation and esterification with acyl chloride having a hydrophobic carbon chain structure to obtain acylated cellulose nanocrystals. The hydrophobicity of the cellulose nanocrystals is improved by the hydrophobic carbon chain. Then, the nanocrystals are mixed, dispersed and polymerized with a polyurethane prepolymer emulsion formed by isocyanate and terminal hydroxyl polyester prepolymer to form a modified polyurethane with an interpenetrating network structure, thereby improving the tear resistance and waterproof performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of leather material technology, specifically relating to a waterproof and tear-resistant modified polyurethane for artificial leather and its preparation method. Background Technology
[0002] Artificial leather is a typical layered composite material, usually composed of two main parts: a surface coating and a base fabric. The surface coating determines the material's appearance, texture, and main surface properties, while the base fabric provides basic mechanical support and dimensional stability. The base fabric, also known as the skeletal layer, is the skeleton layer of the artificial leather, and common types include woven fabrics, knitted fabrics, and non-woven fabrics. Surface coating materials include polymers such as polyvinyl chloride (PVC) and polyurethane. Polyurethane materials, due to their strong structural designability, good elasticity, and wear resistance, have become the mainstream coating material in the artificial leather industry. However, conventional polyurethane still has some significant performance shortcomings in practical applications, limiting its use in more demanding scenarios. One is insufficient waterproof and water-resistant properties. Polyurethane molecular chains contain a large number of polar groups, among which ester groups, ether groups, and urethane groups are prone to hydrolysis reactions when exposed to moisture, especially in high-temperature and high-humidity environments, leading to molecular chain breakage. This manifests as a hardened, brittle coating, surface powdering, or even peeling off—a problem commonly referred to in the industry as hydrolytic aging. In rainy and humid southern regions or outdoor use scenarios, hydrolytic aging is one of the main causes of failure in synthetic leather. Secondly, it has low tear resistance. Tear resistance is an important indicator of the durability of synthetic leather, directly affecting the product's lifespan and safety. Compared to natural leather, polyurethane is far less tear-resistant; under external force, cracks propagate rapidly, eventually leading to the overall breakage of the material.
[0003] Therefore, improving the waterproof and tear-resistant properties of polyurethane materials used in artificial leather is crucial for the application of artificial leather. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention solves the technical problems mentioned in the prior art by mixing, dispersing, and then polymerizing a polyurethane prepolymer emulsion formed from acylated cellulose nanocrystals, isocyanate, and hydroxyl-terminated polyester prepolymers, thereby creating a modified polyurethane with an interpenetrating network structure. Specifically, the technical solution of this invention includes the following:
[0005] One objective of this invention is to provide a method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather, the method comprising the following steps:
[0006] Isocyanate, hydroxyl-terminated polyester and catalyst are mixed and reacted at 60-70℃ for 90-120 min to obtain polyurethane prepolymer;
[0007] After pre-dispersing the chain extender, acylated cellulose nanocrystals and surfactant, they are added to the polyurethane prepolymer and heated to 75-80℃ for 60-90 min. The temperature is then lowered to 40-50℃, and alkali is added to adjust to neutrality. Water is then added to adjust the solid content to 34-36%, followed by emulsification to obtain the modified polyurethane.
[0008] In this invention, the solid content cannot be too high, otherwise the viscosity may increase significantly, the coating surface will dry and seal rapidly when heated, the internal moisture will vaporize when heated, and the water vapor trapped inside the film will break outward, which may easily form pinholes and micro-connected pores, forming water molecule penetration channels, which will reduce the waterproof performance and tear resistance.
[0009] Furthermore, the isocyanate includes hexamethylene diisocyanate. The isocyanate is not suitable for use with a benzene ring structure. Although the hydrophobicity of the benzene ring is beneficial to improving the waterproof performance, the rigid structure of the benzene ring may increase the stress concentration points of the system and thus damage the material properties.
[0010] Furthermore, the method for preparing the hydroxyl-terminated polyester includes the following steps:
[0011] Succinic acid, pentaerythritol, and p-toluenesulfonic acid are mixed in a weight ratio of 6-8:14:0.9-1 and heated to 110-120°C for 2.5-3 hours to obtain pentaerythritol ester.
[0012] Pentaerythritol ester, trimethylolpropane, and p-toluenesulfonic acid are mixed in a weight ratio of 4~4.5:1:0.01~0.015 and heated to 150~160℃ for 4~5 hours to obtain the terminal hydroxyl polyester. In the branching reaction of the terminal hydroxyl polyester, if the reaction time is too long, the branched structure will be too large and the crosslinking will be too dense, which may lead to excessive rigidity and damage to the material properties.
[0013] Furthermore, the catalyst comprises dibutyltin dilaurate.
[0014] Furthermore, the chain extender includes dimethylolpropionic acid, and the chain extender needs to have a carboxyl group for subsequent water emulsification; otherwise, phase separation will occur, which is not conducive to the reaction.
[0015] Furthermore, the preparation method of the acylated cellulose nanocrystals includes the following steps:
[0016] The nucleating agent, acyl chloride and catalyst are mixed in a weight ratio of 1:1.5~2:1~1.5 and heated to 30~40℃ for 2.5~3h to obtain the acylated cellulose nanocrystals.
[0017] Furthermore, the nucleating agent includes cellulose nanocrystals, the acyl chloride includes hexanoyl chloride, and the catalyst includes pyridine; the carbon chain of the acyl chloride cannot be too long, otherwise it will excessively increase the hydrophobicity of the cellulose nanocrystals and be detrimental to the subsequent condensation reaction with the polyurethane prepolymer.
[0018] Furthermore, the average diameter of the cellulose nanocrystals is 50 nm. The diameter of the cellulose nanocrystals cannot be too low, otherwise they will have higher agglomeration, which may result in poor modification effect in this system and make it difficult to uniformly disperse and react with the polyurethane prepolymer.
[0019] Furthermore, the surfactant is composed of Tween 80 and Span 60 in a weight ratio of 1:0.3~0.4. According to the construction system of the present invention, the surfactant cannot be a cationic surfactant, because the positive charge of the cationic surfactant will neutralize the negative charge on the modified polyurethane, thereby causing demulsification, producing a large number of particulate precipitates, and the emulsion will be unusable.
[0020] Further, the weight ratio of isocyanate: hydroxyl-terminated polyester: catalyst: chain extender: acylated cellulose nanocrystals: surfactant is 30~45:100:0.02~0.03:3~9:2.5~4:1.5~2.
[0021] A second objective of this invention is to provide a method for preparing a modified polyurethane that is waterproof and tear-resistant for use in artificial leather.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] This invention constructs a branched hydroxyl-terminated polyester, which is then polymerized with isocyanate and chain extender to obtain a modified polyurethane for artificial leather. The branched structure has a large number of three-dimensionally outward-extending branches, forming physical-chemical nodes distributed in the resin matrix. The three-dimensional branched spatial structure formed by crosslinking after branching can deflect and bifurcate the expanding crack when the material is subjected to tearing force, thus consuming the crack propagation fracture energy. Furthermore, by constructing a multi-functional crosslinking network, it disperses the external force and inhibits crack propagation, thereby improving the tear resistance of the material. However, during testing, it was found that although it possessed a certain degree of tear resistance, its waterproof performance deteriorated. This may be because while the introduction of branched structures can improve tear resistance by dispersing external forces through a three-dimensional network structure, it also disrupts the regularity of polyurethane molecular chains, thereby affecting the crystallinity during polyurethane synthesis. This could lead to an increase in the amorphous regions for water molecule diffusion. Further increasing the degree of branching can increase the crosslinking density and inhibit molecular chain movement, thus achieving waterproof performance. However, excessive branching and resulting dense crosslinking may cause excessive local rigidity, creating stress concentration points that are prone to cracking under external forces, thus compromising tear resistance. Therefore, this invention uses cellulose nanocrystals as a nucleating agent to enhance the crystallinity of polyurethane. The nucleation effect of cellulose nanocrystals improves the crystallinity of polyurethane, resulting in a tightly packed internal structure that hinders water molecule penetration. However, direct use is problematic because cellulose nanocrystals have poor interfacial compatibility with polyurethane, and the surface of cellulose nanocrystals contains numerous hydroxyl groups that can form hydrogen bonds with water molecules. This not only hinders the improvement of waterproof performance but also weakens tear resistance. To this end, the present invention modifies cellulose nanocrystals by acylation and esterification with acyl chloride having a hydrophobic carbon chain structure to obtain acylated cellulose nanocrystals. The hydrophobicity of the cellulose nanocrystals is improved by the hydrophobic carbon chain. Then, the nanocrystals are mixed, dispersed and polymerized with a polyurethane prepolymer emulsion formed by isocyanate and terminal hydroxyl polyester prepolymer to form a modified polyurethane with an interpenetrating network structure, thereby improving the tear resistance and waterproof performance. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below through embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Unless otherwise stated, all raw materials and reagents used in this invention are commercially available or can be prepared by known methods.
[0026] Preparation Example 1
[0027] The preparation process of hydroxyl-terminated polyester is shown below:
[0028] 60g of succinic acid and 140g of pentaerythritol were weighed and added to a flask containing 200mL of dimethylformamide. The mixture was stirred until completely dissolved and homogeneous. Then, 9g of p-toluenesulfonic acid was added and stirred at 200 rpm. A reflux condenser was installed and connected to a water separator. The temperature was then raised to 110℃, and the reaction was stirred at this temperature for 2.5 hours. After the reaction, the product was washed successively with water, 5% sodium carbonate solution, and water. The organic layer was then extracted with ethyl acetate. The organic layer was evaporated under reduced pressure to remove the solvent, yielding pentaerythritol ester. 160g of pentaerythritol ester, 40g of trimethylolpropane, and 0.4g of p-toluenesulfonic acid were weighed and added to a flask containing 200mL of dimethylformamide and 100mL of toluene. The stirring speed was controlled at 150 rpm. Nitrogen gas was then introduced to purge the air from the flask, and the temperature was raised to 150℃, and the reaction was stirred for 4 hours. The pressure was maintained at atmospheric pressure throughout the reaction. After the reaction was completed, dimethylformamide was removed by vacuum distillation to obtain a hydroxyl-terminated polyester.
[0029] Preparation Example 2
[0030] The preparation process of hydroxyl-terminated polyester is shown below:
[0031] 70g of succinic acid and 140g of pentaerythritol were weighed and added to a flask containing 250mL of dimethylformamide. The mixture was stirred until completely dissolved and homogeneous. Then, 9.5g of p-toluenesulfonic acid was added and stirred at 200 rpm. A reflux condenser was installed and connected to a water separator. The temperature was then raised to 110℃, and the reaction was stirred at this temperature for 3 hours. After the reaction, the product was washed successively with water, 5% sodium carbonate solution, and water. The organic layer was then extracted with ethyl acetate. The organic layer was evaporated under reduced pressure to remove the solvent, yielding pentaerythritol ester. 170g of pentaerythritol ester, 40g of trimethylolpropane, and 0.5g of p-toluenesulfonic acid were weighed and added to a flask containing 250mL of dimethylformamide and 100mL of toluene. The stirring speed was controlled at 150 rpm. Nitrogen gas was then introduced to purge the air from the flask, and the temperature was raised to 160℃, and the reaction was stirred for 4 hours. The pressure was maintained at atmospheric pressure throughout the reaction. After the reaction was completed, dimethylformamide was removed by vacuum distillation to obtain a hydroxyl-terminated polyester.
[0032] Preparation Example 3
[0033] The preparation process of hydroxyl-terminated polyester is shown below:
[0034] 80g of succinic acid and 140g of pentaerythritol were weighed and added to a flask containing 300mL of dimethylformamide. The mixture was stirred until completely dissolved and homogeneous. Then, 10g of p-toluenesulfonic acid was added and stirred at a speed of 200 rpm. A reflux condenser was installed and connected to a water separator. The temperature was then raised to 120℃, and the reaction was stirred at this temperature for 3 hours. After the reaction, the product was washed successively with water, 5% sodium carbonate solution, and water. The organic layer was then extracted with ethyl acetate. The organic layer was evaporated under reduced pressure to remove the solvent, yielding pentaerythritol ester. 180g of pentaerythritol ester, 40g of trimethylolpropane, and 0.6g of p-toluenesulfonic acid were weighed and added to a flask containing 300mL of dimethylformamide and 100mL of toluene. The stirring speed was controlled at 150 rpm. Nitrogen gas was then introduced to purge the air from the flask, and the temperature was raised to 160℃, and the reaction was stirred for 5 hours. The pressure was maintained at atmospheric pressure during the reaction. After the reaction, dimethylformamide was removed by vacuum distillation to obtain a hydroxyl-terminated polyester.
[0035] Preparation Example 4
[0036] The preparation process of hydroxyl-terminated polyester is shown below:
[0037] 80g of succinic acid and 140g of pentaerythritol were weighed and added to a flask containing 300mL of dimethylformamide. The mixture was stirred until completely dissolved and homogeneous. Then, 10g of p-toluenesulfonic acid was added and stirred at 200 rpm. A reflux condenser was installed and connected to a water separator. The temperature was then raised to 120℃, and the reaction was stirred for 3 hours. After the reaction, the product was washed sequentially with water, 5% sodium carbonate solution, and water. The organic layer was then extracted with ethyl acetate. The solvent was removed from the organic layer by vacuum evaporation to obtain pentaerythritol ester. 180g of pentaerythritol ester, 40g of trimethylolpropane, and 0.6g of p-toluenesulfonic acid were weighed and added to a flask containing 300mL of dimethylformamide and 100mL of toluene. The stirring speed was controlled at 150 rpm. Nitrogen gas was then introduced to purge air from the flask, and the temperature was raised to 160℃, with stirring for 8 hours. The reaction was carried out at atmospheric pressure. After the reaction, dimethylformamide was removed by vacuum distillation to obtain a hydroxyl-terminated polyester.
[0038] Preparation Example 5
[0039] The preparation method of acylated cellulose nanocrystals includes the following steps:
[0040] 20g of cellulose nanocrystals with an average diameter of 50nm, 50mL of dimethylformamide, and 20g of pyridine were weighed and added to a flask. The mixture was dispersed by ultrasonic power at 400W for 30min, and then the temperature was lowered to 5℃. 30g of hexanoyl chloride was then added. After all the hexanoyl chloride was added, the mixture was heated again to 30℃ and stirred at 400r / min for 2.5h. After the reaction was complete, the product was filtered and washed with water until the pH of the wash liquid reached neutral. The product was then transferred to a vacuum drying oven at 80℃ and dried for 12h to obtain acylated cellulose nanocrystals.
[0041] Preparation Example 6
[0042] The preparation method of acylated cellulose nanocrystals includes the following steps:
[0043] 20g of cellulose nanocrystals with an average diameter of 50nm, 50mL of dimethylformamide, and 25g of pyridine were weighed and added to a flask. The mixture was dispersed by ultrasonic power at 400W for 30min, and then the temperature was lowered to 5℃. 35g of hexanoyl chloride was then added. After all the hexanoyl chloride was added, the mixture was heated again to 35℃ and stirred at 400r / min for 2.5h. After the reaction was completed, the product was filtered and washed with water until the pH of the wash liquid reached neutral. Then, the product was transferred to a vacuum drying oven at 80℃ and dried for 12h to obtain acylated cellulose nanocrystals.
[0044] Preparation Example 7
[0045] The preparation method of acylated cellulose nanocrystals includes the following steps:
[0046] 20g of cellulose nanocrystals with an average diameter of 50nm, 50mL of dimethylformamide, and 30g of pyridine were weighed and added to a flask. The mixture was dispersed by ultrasonic treatment at 400W for 30min, and then the temperature was lowered to 5℃. 40g of hexanoyl chloride was then added. After all the hexanoyl chloride was added, the mixture was heated again to 40℃ and stirred at 400r / min for 3h. After the reaction was complete, the product was filtered and washed with water until the pH of the wash liquid reached neutral. The product was then transferred to a vacuum drying oven at 80℃ and dried for 12h to obtain acylated cellulose nanocrystals.
[0047] Preparation Example 8
[0048] The preparation method of acylated cellulose nanocrystals includes the following steps:
[0049] 20g of cellulose nanocrystals with an average diameter of 50nm, 50mL of dimethylformamide, and 30g of pyridine were weighed and added to a flask. The mixture was dispersed by ultrasonic treatment at 400W for 30min, and then the temperature was lowered to 5℃. 40g of lauroyl chloride was then added. After all the lauroyl chloride was added, the mixture was heated again to 40℃ and stirred at 400r / min for 3h. After the reaction was complete, the product was filtered and washed with water until the pH of the wash liquid reached neutral. The product was then transferred to a vacuum drying oven at 80℃ and dried for 12h to obtain acylated cellulose nanocrystals.
[0050] Preparation Example 9
[0051] The preparation method of acylated cellulose nanocrystals includes the following steps:
[0052] 20g of cellulose nanocrystals with an average diameter of 5nm, 50mL of dimethylformamide, and 30g of pyridine were weighed and added to a flask. The mixture was dispersed by ultrasonic treatment at 400W for 30min, and then the temperature was lowered to 5℃. 40g of hexanoyl chloride was then added. After all the hexanoyl chloride was added, the mixture was heated again to 40℃ and stirred at 400r / min for 3h. After the reaction was complete, the product was filtered and washed with water until the pH of the wash liquid reached neutral. The product was then transferred to a vacuum drying oven at 80℃ and dried for 12h to obtain acylated cellulose nanocrystals.
[0053] Example 1
[0054] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0055] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 1 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 1 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 60°C. At this temperature, 30g of hexamethylene diisocyanate and 0.02g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 90 minutes to obtain a polyurethane prepolymer. Next, 3g of dimethylolpropionic acid, 2.5g of acylated cellulose nanocrystals obtained in Preparation Example 5, 1.15g of Tween 80, and 0.35g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 minutes, and then added to the polyurethane prepolymer. The temperature was further increased to 75°C and the mixture was stirred for 60 minutes. Then, the temperature was cooled to 50°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 34%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0056] Example 2
[0057] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0058] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 2 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 2 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 60°C. At this temperature, 35g of hexamethylene diisocyanate and 0.02g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 100 min to obtain a polyurethane prepolymer. Next, 5g of dimethylolpropionic acid, 3g of acylated cellulose nanocrystals obtained in Preparation Example 6, 1.15g of Tween 80, and 0.35g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 75°C and the mixture was stirred for 70 min. Then, the temperature was cooled to 50°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 34%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0059] Example 3
[0060] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0061] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 40g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 110 minutes to obtain a polyurethane prepolymer. Next, 7g of dimethylolpropionic acid, 3.5g of acylated cellulose nanocrystals obtained in Preparation Example 7, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 minutes, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 80 minutes. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 35%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0062] Example 4
[0063] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0064] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of acylated cellulose nanocrystals obtained in Preparation Example 7, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0065] Comparative Example 1
[0066] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0067] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 4 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 4 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of acylated cellulose nanocrystals obtained in Preparation Example 7, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0068] Comparative Example 2
[0069] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0070] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of acylated cellulose nanocrystals obtained in Preparation Example 8, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0071] Comparative Example 3
[0072] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0073] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of acylated cellulose nanocrystals obtained in Preparation Example 9, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0074] Comparative Example 4
[0075] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0076] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of terephthalic diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of acylated cellulose nanocrystals obtained in Preparation Example 7, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0077] Comparative Example 5
[0078] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0079] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of butanediol, 4g of acylated cellulose nanocrystals obtained in Preparation Example 7, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, after cooling to 40°C and adding deionized water to adjust the solid content to 36%, the mixture was treated with an emulsification speed of 2000 r / min for 40 min. However, severe phase separation was found, and the preparation failed.
[0080] Comparative Example 6
[0081] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0082] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of acylated cellulose nanocrystals obtained in Preparation Example 7, and 2g of hexadecyltrimethylammonium chloride were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. After emulsification at 2000 r / min for 40 min, severe demulsification was found, with a lot of sediment at the bottom, and the preparation failed.
[0083] Comparative Example 7
[0084] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0085] The hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours before use to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 minutes to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid was added to the polyurethane prepolymer, and the temperature was further increased to 80°C and stirred for 90 minutes. The mixture was then cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. Finally, the mixture was emulsified at 2000 rpm for 40 minutes to obtain a modified polyurethane.
[0086] Comparative Example 8
[0087] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0088] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of cellulose nanocrystals with an average diameter of 50nm, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 36%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0089] Comparative Example 9
[0090] The preparation process of a waterproof and tear-resistant modified polyurethane for use in artificial leather is shown below:
[0091] Before use, the hydroxyl-terminated polyester obtained in Preparation Example 3 was subjected to vacuum dehydration at 120°C for 2 hours to remove as much water as possible from the system. Then, 100g of the hydroxyl-terminated polyester obtained in Preparation Example 3 was added to a flask and heated until it was completely melted into a liquid state, and then the temperature was adjusted to 70°C. At this temperature, 45g of hexamethylene diisocyanate and 0.03g of dibutyltin dilaurate were added and mixed, and the stirring speed was adjusted to 200 rpm. The mixture was stirred for 120 min to obtain a polyurethane prepolymer. Next, 9g of dimethylolpropionic acid, 4g of cellulose nanocrystals with an average diameter of 50nm, 1.43g of Tween 80, and 0.57g of Span 60 were pre-dispersed in a high-speed disperser at 1000 rpm for 10 min, and then added to the polyurethane prepolymer. The temperature was further increased to 80°C and the mixture was stirred for 90 min. Then, the temperature was cooled to 40°C, the pH of the reaction system was adjusted to neutral with triethylamine solution, and deionized water was added to adjust the solid content to 45%. After emulsification at 2000 r / min for 40 min, modified polyurethane was obtained.
[0092] The modified polyurethanes obtained in Examples 1-4, Comparative Examples 1-4, and Comparative Examples 7-9 were coated onto release paper with a coating thickness of 0.5 mm. The coated paper was then dried in an oven at 110°C. The samples were then cut into 10 cm × 10 cm pieces and weighed as m1. The samples were then completely immersed in deionized water at 30°C for 24 hours. After wiping off the surface moisture, the samples were weighed as m2. The water absorption rate (%) was calculated as (m2-m1) / m1 × 100%, as shown in Table 1 below.
[0093] Table 1 Water Absorption Rate
[0094]
[0095] The modified polyurethanes obtained in Examples 1-4, Comparative Examples 1-4, and Comparative Examples 7-9 were coated onto release paper with a coating thickness of 0.5 mm. The coated paper was then dried in an oven at 110°C and cut into 10 cm × 10 cm samples. The tear strength test was then performed using a tensile testing machine with a tensile speed of 200 mm / min. The results are shown in Table 2 below.
[0096] Table 2 Tear Strength
[0097]
[0098] As can be seen from Tables 1 and 2 above, the modified polyurethane for artificial leather materials prepared by the present invention through Examples 1 to 4 has good waterproof performance and tear resistance.
[0099] The embodiments described above provide a detailed explanation of the technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Various changes and modifications can be made to the present invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed.
Claims
1. A method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather, characterized in that, The preparation method includes the following steps: Isocyanate, hydroxyl-terminated polyester and catalyst are mixed and reacted to obtain polyurethane prepolymer; Chain extender, acylated cellulose nanocrystals and surfactant are pre-dispersed and added to the polyurethane prepolymer. After heating and reaction, the mixture is adjusted to neutral and then emulsified with water to obtain the modified polyurethane.
2. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 1, characterized in that, The isocyanate includes hexamethylene diisocyanate.
3. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 1, characterized in that, The method for preparing the hydroxyl-terminated polyester includes the following steps: Succinic acid, pentaerythritol, and p-toluenesulfonic acid are mixed in a weight ratio of 6-8:14:0.9-1 and heated to 110-120°C for 2.5-3 hours to obtain pentaerythritol ester. Pentaerythritol ester, trimethylolpropane and p-toluenesulfonic acid are mixed in a weight ratio of 4~4.5:1:0.01~0.015 and heated to 150~160℃ for 4~5 hours to obtain the terminal hydroxyl polyester.
4. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 1, characterized in that, The catalyst includes dibutyltin dilaurate.
5. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 1, characterized in that, The chain extender includes dimethylolpropionic acid.
6. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 1, characterized in that, The preparation method of the acylated cellulose nanocrystals includes the following steps: The nucleating agent, acyl chloride and catalyst are mixed in a weight ratio of 1:1.5~2:1~1.5 and heated to 30~40℃ for 2.5~3h to obtain the acylated cellulose nanocrystals.
7. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 6, characterized in that, The nucleating agent includes cellulose nanocrystals, the acyl chloride includes hexanoyl chloride, and the catalyst includes pyridine.
8. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 1, characterized in that, The surfactant is composed of Tween 80 and Span 60 in a weight ratio of 1:0.3~0.
4.
9. The method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather according to claim 1, characterized in that, The weight ratio of isocyanate: hydroxyl-terminated polyester: catalyst: chain extender: acylated cellulose nanocrystals: surfactant is 30~45:100:0.02~0.03:3~9:2.5~4:1.5~2.
10. A modified polyurethane prepared by a method for preparing a waterproof and tear-resistant modified polyurethane for artificial leather as described in any one of claims 1 to 9.